Implementation of Storytelling Abilities of Early Childhood Teachers in Early Childhood Education Cluster IV, Kacang Panjang, Cempaka Putih, Central Jakarta - Sari, Euis Agung; Puridawaty, Brigita (Kirana Publisher (KNPub), 2025)
This study describes the implementation of storytelling skills of Early Childhood Education teachers on Cluster 4 Early Childhood Education in Kacang Panjang, Cempaka Putih District, Central Jakarta. Storytelling is an important learning method in early childhood education to develop literacy, imagination, and children's social-emotional skills. This study used a survey method in a descriptive study involving 40 Early Childhood Education teachers from 8 educational institutions in the area. Data were obtained through a Yes-No choice test consisting of 22 statement items. The results of data analysis and discussion showed that the implementation of storytelling skills of Early Childhood Education teachers on Cluster 4 Early Childhood Education in Kacang Panjang, Cempaka Putih, Central Jakarta was in the